Development and content validation of a questionnaire to assess the social determinants of mental health in clinical practice - Handerer, Fritz; Kinderman, Peter; Nevard, Imogen; Tai, Sara (Frontiers in Psychiatry, 2024)
There is growing consensus that consideration of the Social Determinants of Mental Health should be at the centre of mental health care provision. To facilitate this, a validated means to assess mental health service users' social contextual information is arguably needed. We therefore developed a questionnaire to assess the Social Determinants of Mental Health in clinical practice. Our guideline-informed development consisted of three steps; i) construct and purpose definition, ii) initial item generation based on the literature, similar questionnaires, and a selection of the ICD-10, iii) evaluation, revision, and content validation of the questionnaire.Initially we developed 249 items that were reduced, revised, and validated in several stages to 73 items. Content validation of the questionnaire was achieved through surveys and focus groups including mental health care service users and professionals. The surveys and focus groups indicated the need for a standardised assessment of adverse social factors and highlighted that the benefits of such an assessment would be a more holistic approach to identifying and addressing fundamental factors involved in the development of mental health difficulties.Importantly, this study also revealed how any assessment of the Social Determinants of Mental Health must prioritise the assessed person having a central role in the process and control over their own data. The focus groups identified contradicting recommendations regarding the most suitable context to administer the questionnaire. The resulting questionnaire can be considered to be theoretically robust and partially validated. Future research is discussed.